Rapid sintering of ceramic solid electrolytes LiZr2(PO4)3 and Li1.2Ca0.1Zr1.9(PO4)3 using a microwave sintering process at low temperatures. Issue 8 (1st June 2019) - Lai, Yanqing; Sun, Zhen; Jiang, Liangxing; Hao, Xiaojing; Jia, Ming; Wang, Li; Liu, Fangyang
Abstract: NASICON-type LiZr2 (PO4 )3 (LZP) has a high bulk ionic conductivity (∼10 −4  S cm −1 ) and a wide electrochemical stability window between 0 and 5.5 V. However, LZP suffers from a problem in which its desirable rhombohedral phase transforms to the triclinic phase (∼10 −8  S cm −1 ) below 50 °C. In this work, we reported a rhombohedral-structured LiZr2 (PO4 )3 (α-LZP) at room temperature with a high total Li-ion conductivity (2.8 × 10 −6  S cm −1 ) by a microwave sintering process. Moreover, this approach realized a drastic reduction in the sintering temperature from the typical 1200 °C–900 °C with only a 4 h holding time. Using this approach, we also demonstrated the successful synthesis of Ca-incorporated Li1.2 Ca0.1 Zr1.9 (PO4 )3 (LCZP) with an ionic conductivity of 1.7 × 10 −5  S cm −1 .